Effects of cell detachment methods on the dielectric properties of adherent and suspension cells. Issue 13 (July 2015) - Mahabadi, Sina; Labeed, Fatima H.; Hughes, Michael P.; Lapizco‐Encinas, Blanca H.
<x xml:space="preserve">Abstract</x> Cell analyses such as flow cytometry, dielectrophoresis, and some patch‐clamp techniques require that cells be in monodisperse suspension in order for analysis to occur. Where cells have a normally adherent phenotype in vivo, this requires that cells be removed from the surface of the culture flask or vessel. This can be achieved in many ways, but most commonly either by the use of a dissociation medium of some form, or by scraping the cells from the surface. Both methods have potential drawbacks; chemical methods may alter the properties of the cells to such a degree that the measurement might be regarded as meaningless, whilst scraping could cause physical damage to the structure of the cells. In this paper, we use dielectrophoresis to analyse the electrical properties of two adherent cell lines detached by multiple methods, and compare these against a control cell line of suspension cells, examined in both the native state and when subject to the same chemical treatments. The results indicate that most chemical agents do not alter the electrophysiology of cells directly, though they may trigger some potential cell deterioration processes such as apoptosis in the cells. This can be observed in the production of apoptotic body‐like particles and the alteration of cytoplasmic conductivity (which has been associated with apoptotic water efflux). However, cells detached by scraping exhibited statistically significant differences in their electrophysiological properties when compared to those detached by the chemical methods, indicating that this method is unsuitable for detachment of adherent cells prior to analysis of isolates suspension cells.